Forms and functions of market squares in small towns of lower Silesia - Borcz, Zuzanna; Niedźwiecka-Filipiak, Irena (Journal of Architecture and Urbanism, 2008)
In the paper market squares in small towns of Lower Silesia region are presented, their area does not exceed 1 ha. For the present work 15 localities were selected: 10 towns and 5 villages which formerly had civic rights. The variety of shapes of market squares mainly resulted from the fact that the towns were founded in a different way. Most of them were formed as completely new settlements, the so-called settlements “on a rough root”, the other ones developed from boroughs or commercial villages. It should be pointed out that the function of a market square is its crucial feature. In the course of time the market square in many towns underwent transformations of its function along with the loss of importance as the central place of a town. Today market places for wholesale as well as for retail trade are designed at other points of a town. An old market square remains till now as an imposing place, although it may also be used as a car park.Concluding, it may be established that market squares played in the past and still play an important role in a town.Mažų žemutinės Silezijos miestelių formos ir funkcijų tyrimasSantrauka. Pateikiami Žemutinės Silezijos miestelių istorinių turgaus aikščių raidos ir šiandieninės situacijos tyrimo rezultatai. Tyrimui buvo parinkti charakteringiausi 1 ha ploto neviršijančių 10 miestelių ir 5 kaimo gyvenviečių, anksčiau turėjusių civilinių teisių, pavyzdžiai. Šio tyrimo tikslas – atskleisti aikščių, praradusių prekybos paskirtį, raidos tendencijas šiandieninės miestų kultūros ir urbanistinės plėtros kontekste. Autorės nagrinėja miestelių turgaus aikščių atsiradimo ir formavimosi urbanistines ir socialines prielaidas, atskleidžia funkcinio konteksto poveikį istoriniam aikštės plano pavidalui ir orientavimui erdvėje, jos architektūrinei kompozicijai. Išryškinami nagrinėjamų aikščių kompoziciniai ryšiai su kitomis svarbiomis visuomeninėmis erdvėmis ir architektūrinėmis dominantėmis. Aprašoma turgaus aikščių funkcinė transformacija, vykusi XX a. daroma išvada, kad buvusių turgaus aikščių lokalizacija miestelio centre ir jų meninė kompozicinė, taip pat ir istorinė vertė nulėmė tai, kad aikštės ir šiandien tebėra svarbios visuomeninės erdvės.Reikšminiai žodžiai: turgaus aikštė, funkcija, forma, miesto centras.First Published Online: 22 May 2013